IMPACT OF SOCIO-ECONOMIC CHANGES FOR COMPETITIVENESS IN THE FOODSERVICE INDUSTRY - Edyta Gheribi; Nataliya Voytovych (Acta Scientiarum Polonorum. Oeconomia, 2018)
The development of the foodservice industry is related to the social and economic changes taking place in last three decades. The sector is sensitive to economic and social trends. The author’s main aim is to define the most important socio-economic changes which took place in Poland as a result of the political and economic transformation after 1989 and the impact which took place in competitiveness in the foodservice industry. The paper used secondary sources of information such as: data of the Główny Urząd Statystyczny (CSO), business reports, and industry newsletters and publications. The research period was the years 1988–2016. A comparative method was applied for the analysis of collected data and materials. Analysis shows that gastronomic business is one of the most vigorous sectors in Poland. Foodservice enterprises show a significant improvement in the quality and variety of services. Social and demographic trends as well as changing values in society and consumer perceptions promote the development of new opportunities and products in the foodservice industry. The foodservice industry is highly competitive.